2015
DOI: 10.1037/a0038711
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ experiences of clinicians’ crying during psychotherapy for eating disorders.

Abstract: Many psychotherapists cry in therapy sessions. Those clinicians who do cry see it as likely to have a positive impact on the therapy or to have no impact, and therapist personality characteristics have not shown reliable associations to crying in therapy. However, it is not known how patients experience therapists' crying, or whether the patient's view of the therapist's characteristics is related to that experience. This study used an online survey, recruiting 202 patients with eating disorders, 188 of whom h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…The second contains questions about crying in general life, and derives questions from the Adult Crying Inventory—Short Form (Vingerhoets, 2001)—a validated measure that describes the frequency, proneness, and influence on mood of crying behavior. The third section, which specifically focuses on crying during therapy sessions, was developed on the basis of items from two prior surveys of therapists’ crying behavior during psychotherapy (Blume-Marcovici, Stolberg, & Khademi, 2013; Tritt, Kelly, & Waller, 2015). It is composed of 21 items: 9 items explore the frequency of crying episodes in therapy within different time periods (from the last session, last 4 weeks, over the last year, etc.…”
Section: Methodsmentioning
confidence: 99%
“…The second contains questions about crying in general life, and derives questions from the Adult Crying Inventory—Short Form (Vingerhoets, 2001)—a validated measure that describes the frequency, proneness, and influence on mood of crying behavior. The third section, which specifically focuses on crying during therapy sessions, was developed on the basis of items from two prior surveys of therapists’ crying behavior during psychotherapy (Blume-Marcovici, Stolberg, & Khademi, 2013; Tritt, Kelly, & Waller, 2015). It is composed of 21 items: 9 items explore the frequency of crying episodes in therapy within different time periods (from the last session, last 4 weeks, over the last year, etc.…”
Section: Methodsmentioning
confidence: 99%
“…In 55% of these experiences, therapists thought that clients were aware of the crying, and those therapists who discussed their crying with their clients reported improved rapport as a result of the crying. Tritt, Kelly, and Waller (2015) surveyed 105 clients with eating disorders whose therapists had cried in therapy. Such crying was generally experienced positively, but clients more often reported a positive impact of crying (greater respect of clients for therapists, increased likelihood of clients expressing emotion, and greater likelihood that clients would engage in therapy in the future) when therapists had a positive demeanor (happiness, firmness, and con-sistency) rather than a negative demeanor (bored, anxious, and angry).…”
Section: Empirical Literature About Therapist Cryingmentioning
confidence: 99%
“…Some studies have examined clients tears in therapy (Capps et al, 2015; Robinson et al, 2015; Zingaretti et al, 2017), but few have studied the clients’ perspective on therapist tears. In one of the few recent studies taking this perspective, Tritt et al (2015) surveyed 202 clients with eating disorders who reported that over half of their therapists had cried at least once in session. Those who had experienced a therapist crying found the experience generally positive; however, their perception of the crying event was impacted by their understanding of the meaning of the therapist’s tears.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the comprehensiveness of the three studies done by Blume-Marcovici et al (2013, 2015, 2016) and by Knox et al (2017), we still know relatively little about psychotherapists’ in-session tears. In addition, of the research done, the majority of responses have been collected through surveys (Tritt, Kelly, & Waller, 2015), presenting a number of limitations for understanding the meaning of the data. In regard to the one study that was qualitative in nature (Knox et al, 2017), participants were made up of exclusively doctoral students, leaving significant gaps in understanding psychotherapists’ tears with more experienced therapists.…”
mentioning
confidence: 99%